Celebrating IWD 2021: Focus on women in gender research and leadership – Iain Wright - Wright, Iain A. (International Livestock Research Institute, 2021)
Iain Wright, ILRI’s deputy director general, discusses his vision and that of the institute in supporting women in gender research and leadership. He notes that ILRI continually provides and seeks to avail opportunities for women advancement not only in career but in all aspects of their lives.